ACCOUNTANTS' READINESS IN IMPLEMENTING SAK-EP: A CASE STUDY OF THE PONUWA COOPERATIVE AT GORONTALO STATE UNIVERSITY - Cintya Azhari Rauf; Denis D. Naru; Riby Tri Hamdoko; Mohammad Agung Tuki; Gufran Djalali; Adi R. Manggi; Sahmin Noholo (PT. Jurnal Center Indonesia Publisher, 2026)
This study examines the readiness of accountants in implementing the Financial Accounting Standards for Private Entities (SAK EP) at the Ponuwa Cooperative of Gorontalo State University using a descriptive qualitative approach through in-depth interviews, observation, and documentation. The results show that the cooperative is administratively ready to prepare financial statements in the form of Business Income (PHU), capital change reports, and balance sheets in accordance with the SAK EP, which is mandatory under Permenkop UKM No. 2 of 2024. Accountants have accounting competencies and practical experience, supported by local IT systems and Excel, as well as internal supervision from supervisory bodies and university facilities. The main obstacles include uncollectible receivables due to double borrowing by members and a tax system based on the previous year's PHU. Overall, the implementation of SAK EP has effectively improved the transparency and accountability of small savings and loan cooperative financial management.